A Candidate High-velocity Exoplanet System in the Galactic Bulge - Sean K. Terry; Jean-Philippe Beaulieu; David P. Bennett; Aparna Bhattacharya; Jon Hulberg; Macy J. Huston; Naoki Koshimoto; Joshua W. Blackman; Ian A. Bond; Andrew A. Cole; Jessica R. Lu; Clément Ranc; et al. (The Astronomical Journal)
We present an analysis of adaptive optics images from the Keck I telescope of the microlensing event MOA-2011-BLG-262. The original discovery paper by Bennett et al. reports two possibilities for the lens system: a nearby gas giant lens with an exomoon companion or a very low-mass star with a planetary companion in the Galactic bulge. The ∼10 yr baseline between the microlensing event and the Keck follow-up observations allows us to detect the faint candidate lens host (star) at K = 22.3 mag and confirm the distant lens system interpretation. The combination of the host star brightness and light curve parameters yields host star and planet masses of M _host = 0.19 ± 0.03 M _⊙ and m _p = 28.92 ± 4.75 M _⊕ at a distance of D _L = 7.49 ± 0.91 kpc. We perform a multiepoch cross reference to Gaia Data Release 3 and measure a transverse velocity for the candidate lens system of v _L = 541.31 ± 65.75 km s ^−1 . We conclude this event consists of the highest-velocity exoplanet system detected to date, and also the lowest-mass microlensing host star with a confirmed mass measurement. The high-velocity nature of the lens system can be definitively confirmed with an additional epoch of high-resolution imaging at any time now. The methods outlined in this work demonstrate that the Roman Galactic Exoplanet Survey will be able to securely measure low-mass host stars in the bulge.